Tissue culture requirements of the evergreen broad-leaved plant Illicium henryi D - Li, Panpan; Yang, Ying; Jiang, Songlin; Chen, Kexin; Xue, Ninghan; Ji, Xingran; Wang, Xiaoge; Ji, Wenli (Frontiers in Plant Science, 2025)
Illicium henryi Diels is a rare wild plant species with limited natural distribution, ecological vulnerability, and challenging cultivation requirements, yet little progress has been made in its introduction and propagation techniques. To address this gap, this study aimed to establish an efficient protocol for its aseptic plantlet production using tissue culture technology. Semi-lignified stem segments with buds, young leaves, sprouting buds, and young shoots bearing buds from the current year were selected as explants, and the effects of different sterilization methods and explant types on disinfection efficiency were systematically evaluated. Based on these findings, suitable basal media were identified for bud induction and leaf-derived callus induction, and the roles of plant growth regulators including 6-BA, NAA, and IBA were further assessed at different stages of bud induction, callus formation, and proliferation. The optimized conditions enabled the successful in vitro regeneration of I. henryi plantlets, with both bud-bearing stem segments and leaf-derived callus showing stable regeneration potential. These results provide a practical method for the artificial propagation of I. henryi in introduced habitats and establish a reliable regeneration system, thereby contributing to its conservation, sustainable utilization, and future tissue culture research in Illicium and related species.